2007
DOI: 10.1021/ja0731470
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Far Red Sensitization of Nanocrystalline TiO2 Films by an Unsymmetrical Squaraine Dye

Abstract: Dye-sensitized solar cells (DSSCs) have attracted significant attention as low-cost alternatives to conventional solid-state photovoltaic devices. [1][2][3] In these cells, the most successful chargetransfer sensitizers employed are ruthenium polypyridyl complexes, yielding 9-11% solar-to-electric power conversion efficiencies under AM 1.5. 4 The majority of the ruthenium complexes reported to date show absorption in the visible region at around 535 nm. Essential for efficient conversion of solar energy by DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
377
0
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 493 publications
(400 citation statements)
references
References 13 publications
13
377
0
6
Order By: Relevance
“…The dyes were selected to allow a broad transparency window in the visible spectrum for the first cell and maximizing the absorption range for the second cell. A squaraine dye coded as SQ1 13 and the black dye (N749) 11 were chosen based on their complementary properties over their absorption spectra. The electrolyte A6141 14 was selected for its electrochemical properties allowing a high current density with low concentration and therefore high light transmission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dyes were selected to allow a broad transparency window in the visible spectrum for the first cell and maximizing the absorption range for the second cell. A squaraine dye coded as SQ1 13 and the black dye (N749) 11 were chosen based on their complementary properties over their absorption spectra. The electrolyte A6141 14 was selected for its electrochemical properties allowing a high current density with low concentration and therefore high light transmission.…”
Section: Methodsmentioning
confidence: 99%
“…All-organic dyes, such as the squaraine dye, have a narrow absorption bandwidth extending into the far red region of the visible spectrum and have demonstrated solar power conversion efficiencies up to 4.5% under AM 1.5. 13 In addition to considerably reducing costs when compared with a ruthenium-based dye, two new distinct tandemcell configurations become available when using this type of dye. First we can propose a trilevel tandem device [ Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Different π-conjugated linker groups such as the -C=C-chain, [9][10][11][12][13]16,24 thiophene units (and its derivatives), 11,[14][15][16][17][18][19][20][21][22]26 etc have also been investigated. In particular two types of acceptor/anchor groups, namely cyanoacrylic acid, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and carboxylic acid [27][28][29] are widely used in organic dyes for DSSC.…”
Section: Introductionmentioning
confidence: 99%
“…It consists in a multiple dyes co-sensitization in order to enlarge photonic response via panchromatic absorption, hence to increase efficiency. There have been already proposed works focalizing on the panchromatic feature of a dye solar cell (Ogura et al, 2009;Yum et al, 2007;Park, 2010). The way to get improvement is by the use of two (up to three) dyes adsorbed on the nanocrystalline titania that are responsible for broad spectral response of the device.…”
Section: Photon Managementmentioning
confidence: 99%
“…It has been considered with particular attention to some organic dyes having complementary spectral response in the red with respect to the ruthenium-based dyes (largely used for standard DSC), such as squaraine (SQ1) (Clifford et al, 2004), cyanine (Pandey et al, 2010), phthalocyanine (Ono et al, 2009), hemicyanine (Cid et al, 2007). Indeed in other studies the co-sensibilization approach has shown high device performances toward red and violet as well in the electromagnetic spectrum (Yao et al, 2003;Kuang et al, 2007;Yum et al, 2007Yum et al, , 2008Clifford et al, 2004). The scope of co-sensitization is to enlarge the absorbance spectrum of the cell toward the Near Infra Red (NIR), thus to increase the Incident Photon to Current Efficiency (IPCE) by enhancing the LHE (Light Harvesting Efficiency) and the efficiency of injection inside the TiO 2 (see IPCE section).…”
Section: Co-sensitizationmentioning
confidence: 99%